Skin advanced glycation end products as biomarkers of photosensitivity in schizophrenia. Issue 1 (31st January 2019) - Tani, Eriko; Ohnuma, Tohru; Hirose, Hitoki; Nakayama, Ken; Mao, Wanyi; Nakadaira, Mariko; Orimo, Narihiro; Yamashita, Hiroki; Takebayashi, Yuto; Miki, Yasue; Katsuta, Narimasa; Nishimon, Shohei; et al.
Abstract: Objectives: Photosensitivity to ultraviolet A (UVA) radiation from sunlight is an important side effect of treatment with antipsychotic agents. However, the pathophysiology of drug‐induced photosensitivity remains unclear. Recent studies demonstrated the accumulation of advanced glycation end products (AGEs), annotated as carbonyl stress, to be associated with the pathophysiology of schizophrenia. In this study, we investigated the relationship among skin AGE levels, minimal response dose (MRD) with UVA for photosensitivity, and the daily dose of antipsychotic agents in patients with schizophrenia and healthy controls. Methods: We enrolled 14 patients with schizophrenia and 14 healthy controls. Measurement of skin AGE levels was conducted with AGE scanner, a fluorometric method for assaying skin AGE levels. Measurement of MRD was conducted with UV irradiation device. Results: Skin AGE levels and MRD at 24, 48, and 72 hr in patients with schizophrenia showed a higher tendency for photosensitivity than in the controls, but the difference was statistically insignificant. Multiple linear regression analysis using skin AGE levels failed to show any influence of independent variables. MRD did not affect skin AGE levels. Conclusions: Photosensitivity to UVA in patients with schizophrenia receiving treatment with antipsychotic agents might not be affected by skin AGE levels.